Participatory Collaboration between University and School in Improving the Quality of Learning in MAS Darussalam Maros - Nashruddin Nashruddin; Sitti Aisyah; Novalia Tanasy; Saparuddin Saparuddin; Mulkiatul Hikmah; Sukmawati Sukmawati; Nurhaliza Nurhaliza; Muh Nasir (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Teacher competency development is an important aspect in improving the quality of learning. The program of Kemahiran Mengajar Aplikasi Lapangan (KEMAL) is designed to provide hands-on teaching experience for students of Universitas Muslim Maros at MAS Darussalam Maros, South Sulawesi. The aim of this activity is to improve pedagogical competence, creativity in learning methods, and classroom management of students through participatory interactions with supervising teachers, principals, and students. The methods used include field observation, preparation of action plans, teaching practice, intensive mentoring, evaluation, and reflection. The results of this community service show an increase in students’ competence in compiling teaching materials, managing classes, and implementing creative learning strategies that are adaptive to students’ character. The active involvement of the school community encourages the creation of a participatory and conducive learning atmosphere. The implications of this activity show that the integration of field practice with a collaborative and reflective approach is effective in shaping the professionalism of prospective teachers and improving the quality of learning in partner schools. The novelty of this program lies in its sustainable and contextual participatory mentoring model.